Health, practical reason and symbolic dimension of internet usages: ethnographic notes on the meanings attributed to reproduction - Vargas, Eliane Portes (Saúde e Sociedade, 2010)
This work analyses the usages of the internet in view of the diffusion of social values associated with the popularization of the human reproduction theme in health websites. These reflections are the result of a broader ethnographic research on 'infertile couples', developed in Rio de Janeiro (2004/2006), which approached the repercussions of involuntary non-reproduction from the viewpoint of upper middle-class couples, having as a starting point their life trajectories. Semi-structured interviews were conducted, as well as the observation of each interview's context, with 16 coupled individuals, all of them employed university graduates with some kind of difficulty in having children. The analytical corpus included the monitoring of internet discussion groups on the subject. This article is circumscribed to the analysis of specific topic relative to the usages of the internet for access to information on the theme of couple's infertility. Due to the diversity of theoretical perspectives on the study of the internet in different disciplinary fields, the analysis provides brief considerations about the particularities of the use of the anthropological approach to the theme. The results show the connection between the popularization of the analyzed theme on the internet, its uses and social conducts. The naturalized conceptions of reproduction are predominant, and the impact of involuntary non-reproduction among couples points to significant gender-related differences. The uses of the internet indicate a self-reflective character in the constitution of individuals and social identities, and point to the connections between the medicalization of the social sphere, the body's reproductive dimension, particularly the feminine body, and the phenomenon of individualization in modern western culture.